Global Economic Prospects 2004 Overview : Realizing the Development Promise of the Doha Agenda - World Bank (Global Economic Prospects, 2003)
The overview of the Global Economic Prospects (GEP) 2004 addresses the Doha Agenda and its effects or failures on global trade integration. The document contains commentary and analysis of international trade and its effects on developing countries and the poor populations of more developed countries. The principle inequities in the global trading system are addressed as well as summarized conclusions from the larger GEP publication